2016
DOI: 10.4103/0974-8490.182918
|View full text |Cite
|
Sign up to set email alerts
|

UP1306, a botanical composition with analgesic and anti-inflammatory effect

Abstract: Background:Pain, one of the cardinal signs of inflammation, is the most common clinical manifestations of arthritis. Conventional pain relief therapy heavily relies on the use of prescription and over the counter nonsteroidal anti-inflammatory drugs as the first line of defense where their long-term usage causes deleterious gastrointestinal and cardiovascular-related side-effects. Hence, there is an equivocal need for evidence-based safer and efficacious alternatives from natural sources to overcome the most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Previously, both UP1306 and UP446 were tested in multiple animal models mainly focused on their symptomatic relief in inflammation and pain. Both showed good anti-inflammatory and antipain activity (Burnett et al, 2007; Tseng-Crank et al, 2010; Altavilla et al, 2009; [ 5 ]). Inflammation plays a central role in osteoarthritis (OA) pathology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, both UP1306 and UP446 were tested in multiple animal models mainly focused on their symptomatic relief in inflammation and pain. Both showed good anti-inflammatory and antipain activity (Burnett et al, 2007; Tseng-Crank et al, 2010; Altavilla et al, 2009; [ 5 ]). Inflammation plays a central role in osteoarthritis (OA) pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Recently we reported a botanical composition designated as UP1306 (a proprietary blend of two bioflavonoid standardized extracts from the heartwood of Acacia catechu and root bark of Morus alba ) with analgesic and anti-inflammatory effects [ 5 ]. UP1306 resulted in 46.3%–53.3% reductions in paw edema and 43.6%–54.8% reductions in pain sensitivity in the carrageenan induced rat paw edema model as well as a 34.4% reduction in visceral pain sensitivity in Writhing's model in mice [ 5 ]. IC 50 (concentration causing 50% inhibition) values of 20.9 μ g/mL, 49.2 μ g/mL, and 11.1 μ g/mL in cyclooxygenase 1 (COX-1), cyclooxygenase 2 (COX-2), and 5-lipoxygenase (5-LOX), respectively, were documented for UP1306 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The most common symptoms of OA are pain, joint stiffness, crepitation on motion and limitation of joint motion, and OA leads to a significantly reduced quality of life. 3 Main risk factors of OA include age, mechanical injury, obesity, joint infection and osteochondrosis.…”
Section: Introductionmentioning
confidence: 99%
“…[11115] Studies conducted by Yeh et al . [11] showed that levels of MMP-1 mRNA, MMP-3, and MMP-13 in human chondrocytes receiving curcumin for 6 h were decreased compared with the control group, showing the reduction of the metalloproteinases synthesis caused by curcumin.…”
Section: Curcuma Longa and Osteoarthritismentioning
confidence: 99%